Analisis Hukum Pidana dan Hukum Pidana Islam Dalam Menerima Barang Gadai Hasil Curian: - Aulia Syahrani Hafiza; M. Rizal (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
In the current era of globalization, there are more crimes that occur and cases that occur in people’s lives, this has a direct effect on the increasing typses of crime rates which are forms of social deviation that are often found insociety. An increasingly widespread crime is the theft of goods, especially electronic goods such as handphone, laptops, televisions, speakers, and others so that the perpetrators can sell or pawn these items in order to remove traces of the victim and gain profit. The purpose of this study is to find out by analyzing how criminal law and Islamic criminal law work in cases of receipt of pawned good resulting from the crime of theft. The method used by researchers is normative legal research, namely legal research based on surves of book materials and secondary sources. The basic of criminal law is used, including articles related to theft, which are regulated in article 362 of the Criminal Code and article 480 of the Criminal Code regarding collection, while in the review of fiqh jinaiyah it was decided that Ta’zir punishment where the judge is the one who is empowered to sentence the perpetrator with the aim of providing a deterrent and educational effect so that criminal behavior does not occur again. Keywords: criminal law, Islamic criminal law, pawning, theft.